Editor's Note = Note du directeur [35, Spring 1995] - Kealey, Gregory S. (Labour / Le Travail, 1995)
The editor apologizes for the deletion of figures as well as an error on page 126 of the article, "Strikes and Class Consciousness," published in the Fall 1994 issue.
Keywords: ERRATA; STRIKES & lockouts